Strategi Pembelajaran IPS dalam Konteks Kurikulum 2013 Edisi Revisi dengan Konsep Merdeka Belajar - Sanra, Riki; Adisel, Adisel; Merdiansyah, Muhammad; Gusliana, Rina Minita; Azzarah, Afifah Khuzaimah; Ilahi, Diara Ressi Nurul (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to determine the social studies learning strategy in the context of an appropriate independent learning curriculum. The method used in this study using a qualitative description method. The results of the research, social studies learning strategies in the context of the revised 2013 curriculum with the concept of independent learning are considered to be effective and interrelated, because students can think critically, express their opinions, make decisions and can understand situations. The concept of independent self-study can be applied in joint learning with the 2013 curriculum. In conclusion, the implementation of social studies learning strategies in the context of the revised 2013 curriculum has been quite effective, as well as the application of the concept of independent learning that is relevant to the implementation of the 2013 curriculum in producing students according to national education goals. Keywords: 2013 Curriculum, Freedom to Learn, Learning Strategy